FACTORS AFFECTING THE EVENT OF ANEMIA IN HIGH SCHOOL STUDENTS - Anggoro, Sarni (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Anemia is a condition with hemoglobin and erythrocyte levels lower than normal. Iron nutrient anemia in adolescent girls is at higher risk because it causes a person to experience a decrease in endurance so he is susceptible to health problems. This study aims to determine what factors influence the incidence of anemia in class X students of SMA Negeri 1 Kalibawang. This research uses analytic survey type with cross sectional approach. Sampling using total sampling, with a sample of 69 students. The research instrument used a questionnaire and a check tool for hemoglobin levels. The questionnaire was tested for validity using Pearson product moment valid data obtained by r count> r table (0.329) on all four questionnaires. Reliability test using Cronbach alpha showed reliable results with a value of ? = 0.746> 0.6. Data analysis using chi square test. The results of this study, of 69 students there were 14 (20.3%) with abnormal hemoglobin levels and 55 (79.7%) with normal hemoglobin levels. After being tested using chi square there was an influence of knowledge with value (p = 0.003), attitude (p = 0.046), diet (p = 0.003), and family income (p = 0.025) with the incidence of anemia. Anemia in class X students of SMA Negeri 1 Kalibawang is influenced by several factors including knowledge, attitudes, eating patterns, and family income.